Establishment of an induced pluripotent stem cell model of Hirschsrpung disease, a congenital condition of the enteric nervous system, from a patient carrying a novel RET mutation. Issue 12 (15th August 2018) - Wang, Yong; Lai, Xingqiang; Huang, Lihua; Liu, Guangjian; Zai, Zhicheng; Zhu, Deli; Zhang, Yan; Liang, Zijian; Yao, Zhiguang; Chen, Yunpei; Wen, Zhe; Xia, Huimin
Abstract : Hirschsprung disease (HSCR) is a complex genetic disorder of the enteric nervous system that is characterized by a complete loss of the neuronal ganglion cells in the intestinal tract. It is one of the most frequent causes of congenital intestinal obstruction and more than 80% of the causative mutations are in RET. Here, we identified a new RET mutation in a patient and established a cell model that can be used to elucidate the pathogenesis of HSCR. Peripheral blood was collected from a patient who was clinically and pathologically diagnosed with HSCR with a heterozygous deletion mutation (c.180delT; p.Glu61ArgfsX163) in exon 2 of RET. Patient-derived induced pluripotent stem cell (iPSC) lines were generated from dermal fibroblasts. Using immunofluorescence staining and RT-PCR, we showed that the generated iPSCs expressed the pluripotency markers OCT4, SSEA4, SOX2, TRA-1-60, and NANOG. We also showed that the HSCR-iPSCs could differentiate into cells from all three germ layers by spontaneous in-vitro differentiation. In addition, 3 months after the administration of a subcutaneous injection of these iPSCs into nude mice, teratomas with all three germ layers were observed. We identified a new RET gene mutation causing HSCR and successfully established a human iPSC line from an HSCR patient carrying this novel RET mutation, which could be useful in pathogenesis studies of HSCR.